PEMIKIRAN DAN GERAKAN PURITANISME DAN FUNDAMENTALISME DALAM ISLAM: ANALISIS HISTORIS, EPISTEMOLOGIS, DAN DINAMIKA KONTEMPORER - Iklilullah Iklilullah; Zainuddin Syarif (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The phenomena of puritanism and fundamentalism in Islam have become central issues in the dynamics of contemporary religious thought and movements. The urgency of this research lies in the need to comprehensively understand both currents of thought, given the often overlapping use of terms and the increasing relevance of both in the social, cultural, and political contexts of modern Muslims. This research aims to analyze the historical roots, epistemological characteristics, and development of the puritanism and fundamentalism movements in Islam, while also explaining the similarities, differences, and conceptual relationships between them. The research method uses a descriptive qualitative approach through library research, with a search for relevant classical and contemporary literature. The results show that puritanism is rooted in efforts to purify teachings and reject religious practices deemed deviant, while fundamentalism developed in response to modernity and colonialism by emphasizing the application of sharia as the basis of socio-political order. This research also finds common ground in the form of scripturalism and a return to the source text, although the context of the movements and the ideological orientations of the two differ.